An Analysis on YEKDEM Program Implemented in Turkey - Erdem, Murat (My University, 2025)
This study examines the Renewable Energy Resources Support Mechanism (YEKDEM) implemented in Turkey for solar energy. Within this context, the appropriateness of the incentive amounts provided through the YEKDEM application was analyzed. For this purpose, the current formulation calculated the effects of changing the coefficients of the Exchange Rate, PPI, and CPI values in the mathematical equation, as well as the total incentive amounts for certain years. In the study, it was assumed that the weather was entirely sunny when calculating solar radiation. The effects of the incentive amounts, profit-loss scenarios, and the payback period for plant investors were presented. The formula that offers the highest incentive amount for investors is the one with coefficients of 30%-30%-20%-20%. Annual earnings vary between US$ 15,928 and US$ 146,176. Payback periods range from 5.9 to 54 years, depending on the use of credit and equity.
Keywords: YEKDEM; Solar energy; Energy policy; Energy economics; Solar power plants